2019
DOI: 10.1002/cctc.201900037
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Photocatalytic Hydrocarbon Oxidation by Uranyl Complexes

Abstract: Controlled, photocatalytic C−H bond activations are key reactions in the toolkits of the modern synthetic chemist. While it is known that the uranyl(VI) ion, [UVIO2]2+, the environmentally dominant form of uranium, is photoactive, most literature examines its luminescent properties, neglecting its potential synthetic utility for photocatalytic C−H bond cleavage. Here, we synthesise and fully characterise an air‐stable and hydrocarbon‐soluble uranyl phenanthroline complex, [UVIO2(NO3)2(Ph2phen)], UPh2phen, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 34 publications
(37 reference statements)
0
39
0
Order By: Relevance
“…A recent exploration of hydrolytically as well as air‐stable uranyl phenanthroline complex, [UO 2 (NO 3 ) 2 (Ph 2 phen)] (Ph 2 phen = 4,7‐diphenyl‐1,10‐phenanthroline) due to Arnold et al shows the high degree of photocatalytic activity toward the oxidation of organic substrates via controlled C–H bond cleavage. [ 64 ] It has better selectivity and a higher rate of conversions than the commercially available [UO 2 (NO 3 ) 2 (H 2 O) 2 ] · 4H 2 O complex, attributed to ligand‐mediated electronic effects. The scope of this transformation has been extended to a range of substrates.…”
Section: Light‐driven Catalysis Using Uo22+ Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent exploration of hydrolytically as well as air‐stable uranyl phenanthroline complex, [UO 2 (NO 3 ) 2 (Ph 2 phen)] (Ph 2 phen = 4,7‐diphenyl‐1,10‐phenanthroline) due to Arnold et al shows the high degree of photocatalytic activity toward the oxidation of organic substrates via controlled C–H bond cleavage. [ 64 ] It has better selectivity and a higher rate of conversions than the commercially available [UO 2 (NO 3 ) 2 (H 2 O) 2 ] · 4H 2 O complex, attributed to ligand‐mediated electronic effects. The scope of this transformation has been extended to a range of substrates.…”
Section: Light‐driven Catalysis Using Uo22+ Speciesmentioning
confidence: 99%
“…Substrates having benzylic C–H sites such as toluene, triphenylmethane, indane, and isochroman exhibit highest improvements in oxidation while using the UO 2 (NO 3 ) 2 (Ph 2 phen) as catalyst. [ 64 ] Mostly, ketones are preferentially produced over other oxygenated products.…”
Section: Light‐driven Catalysis Using Uo22+ Speciesmentioning
confidence: 99%
“…Very recently, Jiang and co‐workers reported a selective and compatible oxidation of sulfides for the synthesis of sulfones and sulfoxides by using UO 2 (OAc) 2 ⋅ 2H 2 O as photocatalyst and molecular oxygen [17] . Concurrently, Arnold [18] and Takao [19] and their co‐workers demonstrated the photocatalytic oxygenation of hydrocarbons in the presence of a uranyl complex and visible‐light irradiation. In general, these remarkable, but few contributions highlight the novelty and importance of unexplored uranyl photochemistry.…”
Section: Introductionmentioning
confidence: 98%
“…Next, the effect of solventw as surveyed, and CH 3 CN was found to be the most suitable solvent (cf. entries 9a nd[17][18][19][20][21].S ubsequently,w ea ttempted to perform the reactionu nder air,a nd found that the result wasi nferior to that obtained under argon (cf. entries 9a nd 22).…”
mentioning
confidence: 99%
“…Polly has received a variety of awards and prizes including the RSC Wilkinson prize in 2018, the Lord Kelvin Medal 2017, which is the senior prize for the physical sciences awarded by the Royal Society of Edinburgh, the Seaborg Lectureship 2015 (UC Berkeley, USA), and the Royal Society′s Rosalind Franklin award in 2012. She made the film ′A Chemical Imbalance′, a call to action for simple changes to achieve equality of opportunity in science, and was awarded an OBE in the Queen's birthday honors in 2017 for her contributions to chemistry and women in STEM …”
mentioning
confidence: 99%